Influence of heavy metals on rhizosphere microbial communities of Siam weed (Chromolaena odorata (L.)) using a 16S rRNA gene amplicon sequencing approach - Ruangdech, Thanyaporn; Wongphatcharachai, Manoosak; Staley, Christopher; Sadowsky, Michael J.; Sajjaphan, Kannika (Agriculture and Natural Resources, 2017)
A 16S rRNA amplicon sequencing approach was used to assess the impacts of cadmium (Cd) and zinc (Zn) contamination on populations of rhizobacteria on Siam weed (Chromolaena odorata (L.)). Bacterial communities were characterized using the Illumina MiSeq platform and the V6 hypervariable region of the 16S rRNA gene. Among the 54,026 unique operational taxonomic units (OTUs) identified, 99.7% were classified as bacteria and the rest were classified as archaea. Several dominant bacterial phyla were observed in all samples-Proteobacteria, Actinobacteria, Acidobacteria, Firmicutes and Bacteroidetes. These five phyla accounted for 89.2% of all OTUs identified among all sites, and only two OTUs could not be classified to a phylum. Comparison among samples containing low and high levels of Cd contamination using nonparametric Shannon and Shannon diversity indices showed that soils with low levels of diversity had a higher level of Cd (p < 0.05). These results indicated that levels of Cd may significantly alter bacterial species selection. The Cd- and Zn-resistant bacteria from each sample were subjected to heavymetal minimum inhibitory concentration (MIC) analyses. The MIC values obtained from 1152 isolates were used to individually analyze the pattern of gene function using the BioNumerics software. The results of this analysis showed that 26.7% of the bacteria were resistant to Cd concentrations up to 320 mg/L and only 2.3% of bacteria were resistant to Zn at concentrations up to 3200 mg/L. The MIC analyses indicated that the number of resistant bacteria decreased with increasing metal concentrations and those bacteria resistant to Cd and Zn may contain more than one group of metal-resistance genes.